Mapping surgical practice decision making: an interview study to evaluate decisions in surgical care. - Jacklin, R; Sevdalis, N; Darzi, A; Vincent, C (2008)
BACKGROUND: Training surgeons in vital decision-making skills remains unstructured. We aimed to map a process of care from the perspective of surgical decision making and test whether it could be deconstructed into an accessible format for trainees. METHODS: Semistructured interviews were conducted with 10 experienced surgeons by using symptomatic gallstones as a clinical exemplar. Data were analyzed by 2 independent reviewers to identify decisions, cues, and decision rules, with further thematic analysis of selected decisions. RESULTS: Eighteen specific decisions were identified in 6 or more transcripts, with significant interreviewer reliability (Spearman's rho = .65, P = .004, n = 17, 1 outlier excluded). These were arranged to form a "decision map." Two main decision strategies were described. CONCLUSIONS: We identified and mapped the decisions made in the care of patients with symptomatic gallstone disease. The interpretation of competency at any procedure should include the surgeon's ability to make appropriate decisions at all stages of patient care.